1969
DOI: 10.1111/j.1471-4159.1969.tb05938.x
|View full text |Cite
|
Sign up to set email alerts
|

THE MEASUREMENT OF TRIGLYCERIDE IN BRAIN AND THE METABOLISM OF BRAIN TRIGLYCERIDE IN VITRO

Abstract: Abstract— Triglyceride has been isolated from brain by thin‐layer chromatography and determined by absorption of the carbonyl group at 1740 cm−1. The means of yields from whole mouse brain, whole rat brain, rat brain grey matter, rat brain stem, and incubated slices of rat brain cortex were 0.15–0.17 μmole/g tissue. The distribution of fatty esters varied from preparation to preparation. Palmitate, stearate and oleate usually occurred in greatest amounts. Hydrolysis of a preparation of triglyceride from whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

1975
1975
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Those authors concluded that the increase in glycerol reflected membrane phospholipid breakdown as glycerol is an end product of membrane phospholipid hydrolysis and as other possible sources were not likely. Thus triglycerides are only found in trace amounts in brain tissue27 28 and during ischaemia carbohydrate stores are quantitatively transformed into lactate 29. Although the transport mechanisms of glycerol between the extracellular and intracellular compartments are not known, we assume that the increases of interstitial glycerol found in this study reflect the same phenomenon as in experimental brain ischaemia—that is, membrane phospholipid degradation.…”
Section: Discussionmentioning
confidence: 50%
“…Those authors concluded that the increase in glycerol reflected membrane phospholipid breakdown as glycerol is an end product of membrane phospholipid hydrolysis and as other possible sources were not likely. Thus triglycerides are only found in trace amounts in brain tissue27 28 and during ischaemia carbohydrate stores are quantitatively transformed into lactate 29. Although the transport mechanisms of glycerol between the extracellular and intracellular compartments are not known, we assume that the increases of interstitial glycerol found in this study reflect the same phenomenon as in experimental brain ischaemia—that is, membrane phospholipid degradation.…”
Section: Discussionmentioning
confidence: 50%
“…Some of the abnormalities in lipid composition that we report in this study may contribute to this resistance. For example, the decreased brain triacylglycerol concentration in the COX-2 2/2 mouse may increase its resistance to ischemia/reperfusion damage (9,12), because triacylglycerol can be a source of nutrient fatty acids for brain phospholipid biosynthesis (35)(36)(37) and its concentration is increased in cerebral ischemia (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Since palmitate was elongated and desaturated by brain slices only to a slight extent, this may restrict the acylation of radioactive fatty acid into the glyceride fraction. It has been suggested that the small pool of triglyceride present in brain has a high rate of turnover of the acyl moiety (ROWE, 1969) thereby making acyl groups available for further metabolism by elongation or desaturation (MENKES, 1971). Over the time period used in this study (1-5 h) incor-poration of radioactivity into glycerides was always greater than into phospholipids.…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which palmitate derived from the turnover of specific lipid types e.g. triglyceride (ROWE, 1969) or phosphatidylcholine (SUN & HORROCKS, 1971) contributes to the pool of free fatty acid (synthesized de nouo or from exogenous fatty acid) is difficult to assess. The turnover of esterified fatty acid may constitute a second pool of membrane-bound fatty acid, distinct from the pool of free fatty acids synthesized in the cell cytoplasm, which could undergo different metabolic reaction sequences to the free fatty acid in the cell cytoplasm.…”
Section: Discussionmentioning
confidence: 99%